Transition-Aged Youth Who Are Homeless and Misuse Substances: A Qualitative Study of Service Needs. Issue 47 (2nd November 2021) - DeHart, Dana D.; Anderson, Brandi; Martin, Jeremy
Abstract: This study examined the service needs of transition-aged (16-25), homeless youth via group and individual interviews with 22 human service providers and a focus group of 17 transition-aged, homeless youth who were engaged in treatment for substance misuse. Qualitative analyses examined service needs, challenges in addressing these, and intersection with youths' pathways into and out of homelessness. Findings have implications for enhanced networks among service providers to meet the multifaceted needs of this vulnerable population. Pathways into homelessness included unstable homes and involvement in carceral systems such as the foster care and juvenile legal system. Logistical needs of youth included housing, employment, education, transportation, legal aid, obtaining documents, and food security. Mental health needs include substance misuse treatment and recovery services, treatment for co-occurring mental illness and substance use disorders, trauma-informed approaches to care, services for LGBTQ + youth, and coping/life skills. Medical needs included those around sexual health and family planning, dental and vision care, primary care, immunizations, and chronic disease management. Recommendations are provided for research, practice, and policy concerning transition-aged, homeless youth who misuse substances; these include approaches at the individual and family level as well as those that address systemic barriers and structural vulnerability for youth.